Static Body Weight Distribution and Girth Measurements Over Time in Dogs After Acute Thoracolumbar Intervertebral Disc Extrusion - Amaral Marrero, Natalia P.; Thomovsky, Stephanie A.; Linder, Jessica E.; Bowditch, Jessica; Lind, Mallory; Kazmierczak, Kristine A.; Moore, George E.; Lewis, Melissa J. (Frontiers in Veterinary Science, 2022)
Dogs with thoracolumbar intervertebral disc extrusion (TL-IVDE) can exhibit variable neurologic deficits after decompressive surgery. The objectives of this study were to quantify changes in static weight distribution (SWD) and limb and body circumference over time in dogs recovering from surgery for TL-IVDE. Dogs with acute TL-IVDE were prospectively evaluated at baseline (48-72 hours post-operatively), 2, 4, 8, and 12 weeks post-operatively. Commercially-available digital scales were used to measure weight distributed to the pelvic limbs (PL%) and asymmetry between left and right pelvic limbs (LRA), each expressed as a percentage of total body weight. Trunk and thigh circumference measurements were performed using a spring-loaded tape measurement device. Measurements were performed in triplicate, compared to neurologically normal small breed control dogs and analyzed for changes over time. P<0.05 was significant. Twenty-one dogs were enrolled; 18 regained ambulation and 3 did not by study completion. PL% increased from 27.6% at baseline to 30.7% at 12 weeks but remained lower than in control dogs (37%) at all time points (p<0.0001), even excluding dogs still non-ambulatory at 12 weeks (p<0.025). LRA was similar to the control dogs, and did not have an association with surgical side. Caudal trunk girth decreased over time to 95% of baseline (p=0.0002), but this was no longer significant after accounting for reductions in body weight (p=0.30). Forward shifting of body weight persisted in dogs with TL-IVDE 12 weeks after surgery even among ambulatory dogs. SWD and circumference measurements could provide additional objective measures to monitor recovery.